2009
DOI: 10.1002/ab.20329
|View full text |Cite
|
Sign up to set email alerts
|

The influence of violent and nonviolent computer games on implicit measures of aggressiveness

Abstract: We examined the causal relationship between playing violent video games and increases in aggressiveness by using implicit measures of aggressiveness, which have become important for accurately predicting impulsive behavioral tendencies. Ninety-six adults were randomly assigned to play one of three versions of a computer game that differed only with regard to game content (violent, peaceful, or abstract game), or to work on a reading task. In the games the environmental context, mouse gestures, and physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
93
2
10

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 67 publications
7
93
2
10
Order By: Relevance
“…This disposition is thought to play a key role in aggression tendency, particularly with impulsive aggression (Bluemke et al, 2009), a notion supported by both the GAM and the Integrated Model. Using a student sample Bluemke et al (2009) found it correlated with stable trait aggression measures.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…This disposition is thought to play a key role in aggression tendency, particularly with impulsive aggression (Bluemke et al, 2009), a notion supported by both the GAM and the Integrated Model. Using a student sample Bluemke et al (2009) found it correlated with stable trait aggression measures.…”
mentioning
confidence: 98%
“…This disposition is thought to play a key role in aggression tendency, particularly with impulsive aggression (Bluemke et al, 2009), a notion supported by both the GAM and the Integrated Model. Using a student sample Bluemke et al (2009) found it correlated with stable trait aggression measures. Bluemke et al (2009) noted a positive correlation between implicit cognitive aggression and overall trait, physical and angry aggression but not in relation to verbal aggression and hostility.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…electro shocks, cold water), or insults from the experimenter (Anderson & Bushmann, 1997;Richtelin, Richardson, & Mason, 2010). Other experiments have used media vi olence to induce aggression, such as computer games (Bluemke, Friedrich, & Zumbach, 2009) and violent films (Bushmann, 1995;Linz, Donnerstein, & Adams, 1989). Although these potentially stimulate appetitive aggression, they do not distinguish subtypes of aggression, complicating outcomes.…”
Section: Introductionmentioning
confidence: 99%